2021
DOI: 10.3389/fonc.2021.650673
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of an Immune Cell Infiltration Score to Help Predict the Prognosis and Chemotherapy Responsiveness of Gastric Cancer Patients

Abstract: The immune microenvironment plays a critical role in tumor biology. The molecular profiles of immune components and related genes are of tremendous value for the study of primary resistance to immune checkpoint blockers (ICBs) for gastric cancer (GC) and serve as prognostic biomarkers to predict GC survival. Recent studies have revealed that tumor immune cell infiltration (ICI) is an indicator of the survival and responsiveness to chemotherapy in GC patients. Here, we describe the immune cell landscape based o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 59 publications
0
22
0
Order By: Relevance
“…Prognostic signatures based on ferroptosis-related lncRNA, immune-related lncRNA and helicobacter pylori infectionrelated lncRNA were proved to have preferable prognosis prediction functions in GC (Ma et al, 2021;Pan J. et al, 2021;Wei et al, 2021;Xin et al, 2021). Apart from this, lncRNAs could be used for subtype identification and therapy response prediction of GC Jiang et al, 2021b). LncRNAs have also been reported to modulate immunity (Yu et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Prognostic signatures based on ferroptosis-related lncRNA, immune-related lncRNA and helicobacter pylori infectionrelated lncRNA were proved to have preferable prognosis prediction functions in GC (Ma et al, 2021;Pan J. et al, 2021;Wei et al, 2021;Xin et al, 2021). Apart from this, lncRNAs could be used for subtype identification and therapy response prediction of GC Jiang et al, 2021b). LncRNAs have also been reported to modulate immunity (Yu et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…This process can reduce the infidelity of CIBERSORT results ( 53 ). This score system is shown to be more stable and may not be influenced by a single or several gene expression ( 54 56 ). Besides, the established ICI scoring system can also provide valuable information on designing of the optional therapeutic regimen.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, GSEA revealed that CHEK1, CDC25A and FOXK1 were enriched in the cell cycle, pathways in cancer, and the P53 signaling pathway, which are correlated with cancer pathogenesis. Accumulating studies (Jiang et al, 2021;Zhou et al, 2021) have found that tumor-infiltrating immune cells, including B cells, CD4+/ CD8+ T cells, macrophages, neutrophils and dendritic cells, affect the efficacy of chemotherapy and immunotherapy and thus affect the prognosis of patients. Our work showed that the ceRNA regulatory network was significantly related to the infiltration of immune cells and the expression of immune checkpoints.…”
Section: Discussionmentioning
confidence: 99%